Creative Adaptive Criminal Entrepreneurs from Africa and Human Trafficking in Belgium: Case Studies of Traffickers from Nigeria and Morocco - Leman, Johan; Janssens, Stef (International Journal of Criminology and Sociology, 2013)
The article is based on 48 Belgian judicial files (27 Nigerian and 21 Moroccan ones), that concern the practices that created victims of human trafficking from Nigeria and Morocco in Belgium and some neighbouring countries. We discover that the most efficient criminal entrepreneurs are the very flexible ones, who continuously adapt, learn, dare to diversify, and sometimes also to internationalize (but mostly with African partners). An important difference with the Eastern European criminals whom we studied in former research, is that the Africans most of the time do not look for coverage of their practices through legal firms. Their learning practice remains re-active; until 2012 it does not really become pro-active. There is no pro-active longer term vision and no intention to create legal structures that hide their praxis.